Pengendalian Banjir Sungai Bottolai Pada Perumahan Graha Hibridah Amaro Kabupaten Barru - Lutfian, Muhammad Alif; Yusuf, Andi Rumpang; Syahrir, Suryani (Program Studi Teknik Sipil Universitas Bosowa, 2024)
With the frequent occurrence of floods at the Graha Hibridah Amaro Housing Complex, Barru Regency, it is necessary to have an effort in the form of a flood control system to minimize flood events which result in material losses and claim lives and damage existing infrastructure around the watershed. The analysis carried out in this thesis is limited to the Bottolai River, Barru District, Barru Regency. The purpose of this research is to find a solution to the flood disaster that occurred in the area. This research was conducted by collecting secondary data in the form of watershed maps and rainfall data at the nearest rainfall station. The data is to determine the return period of rainfall and flood discharge of the river. After that, by analyzing the capacity of the river channel, it can be concluded for the flood control system in the area. From the results of the analysis, it was found that the peak flood discharge using the Nakasyu method was 36.09 m3/sec, while the capacity of the Kanci River channel was 13.5 m3/sec. From the results of this analysis it can be concluded that the Kanci River has the potential to flood. So it is necessary to find a solution for flood control in the form of changing the dimensions of the drainage channel.